Digital Branding of Tourism Promotion: Gastrodiplomacy In The Digital Age - Awanis Akalili; Arselma Trus'tee Audrey; Yanuar Galih Wiryawan (Universitas Negeri Yogyakarta, 2025)
The digital landscape is transforming perspectives and approaches within the modern tourism industry. In previous eras, the approach to tourism was centered on exploiting natural beauty. Today, the focus has shifted towards the narrative of tourist experiences. Furthermore, the rising popularity of culinary tourism through social media and mass media channels has played a role in this paradigm shift. One country with popular culinary products is Thailand. This research will analyze how the phenomenon of culinary promotion in Thailand can be seen as a practice of gastrodiplomacy executed through a digital branding strategy. This study employs a qualitative research approach with a case study strategy. Data was collected using an open-ended online questionnaire. Research informants were selected using a purposive sampling technique. The criteria for informants were undergraduate students aged 18-25 who are active users of various social media platforms. This study found that culinary-based tourism promotion strategies on digital platforms can persuade audiences. Culinary content on digital media not only fosters the intention to travel but also awakens gastronomic curiosity—the desire to experience cuisine firsthand in its place of origin. Two key elements of content quality were identified: the authenticity of personal storytelling and visual quality. Both elements play a role in the promotional effectiveness of culinary content. The anatomy of the most appealing advertisement for the audience is content that can present a complete experiential narrative, centers on the authenticity of street food, and values the process of creating culinary products as a cultural art form. These findings offer a strategic model for countries with similar potential, particularly Indonesia, to optimize gastronomy as a tool for tourism promotion on the global digital stage.